Game activity and blood lactate in men's elite water-polo players - Melchiorri, G.; Castagna, C.; Sorge, R.; Bonifazi, M. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine game demands during highly competitive men's water-polo games after the introduction of the new Federation International Natation Association (FINA) rules. Participants of this study were 77 outfield international level men's water-polo players (age 25.9 ± 4.5 years, height 188 ± 4.5 cm, body mass 93 ± 10.9 kg). Game earlobe blood lactate, speed, and distance covered (semiautomatic image recognition system) were measured during 6 highly competitive matches (FINA International Tournament). In the game, players covered 1,613 ± 150 m (n = 68). This corresponds to a mean coverage rate of 54 ± 5.8 m/min (n = 68). At speeds faster than 1.4 m/s (high-intensity swimming), players covered 44% of the total distance. A significant decrease in coverage rate was detected during the final stage of the game. Mean blood-lactate concentration was 7.7 ± 1.0 mmol/L (range 2.2-14.3). Center Defenders (1,816 ± 496 m) covered significantly (p < 0.05) more distance swimming compared to Field (1,676 ± 348 m) and Center-Forward (1,317 ± 281 m) players. Mean match blood-lactate concentrations for Center Forwards, Center Defenders, and Field Players were 11.2 ± 1.0 (3-14.3), 6.7 ± 0.9 (1.4-8), and 5.3 ± 0.9 mmol/L (2.2-11.9), respectively. This study confirmed the high-intensity nature of male elite level water polo showing remarkable role-dependent game demands. As a result, strength and conditioning interventions should be individualized and mainly address intermittent high-intensity endurance and anaerobic fitness.